Objects, models, components, patterns 49th International Conference, TOOLS 2011, Zurich, Switzerland, June 28-30, 2011. Proceedings - Bishop, J. M. (Judith Mary) 1951-; Vallecillo, Antonio 1962- (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 49th International Conference on Objects, Models, Components, Patterns, held in Zurich, Switzerland, in June 2011. The 19 revised full papers presented together with the abstracts of 2 invited papers were carefully reviewed and selected from a total of 68 submissions. The papers discuss all aspects of object technology and related fields, in particular model-based development, component-based development, language implementation and patterns, in a holistic way. The conference has a strong practical bias, without losing sight of the importance of correctness and performance.